MANAJEMEN KURIKULUM MERDEKA PADA PENDIDIKAN INKLUSIF - Jannatul Firdausi Nuzula; Muhammad Sabri Latif; Marno Marno; Munirul Abidin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
:  The implementation of inclusive education in Islamic educational institutions in Indonesia is far from perfect, necessitating a more in-depth analysis from various aspects as an integrated system, particularly the curriculum. This study aims to explain how the management of the independent curriculum is carried out, from planning, organizing, implementing, and evaluating, in inclusive Islamic educational institutions. The research method used is library research, which involves reviewing previously published literature related to the research theme. This study focuses on the management of the independent learning curriculum in Islamic educational institutions that are providing or planning to provide inclusive services. The study finds that in planning, implementing, organizing, and evaluating students with special needs, the approach must be adjusted to their abilities, developed by educators through creative and innovative differentiated learning, with the support of the students' parents.